Impact of game elements on tennis match outcome in Wimbledon and Roland Garros 2009 - Katic, R.; Milat, S.; Zagorac, N.; Durovic, N. (Collegium Antropologicum, 2011)
The aim of the study was to assess the correlation among particular tennis game elements and match outcomes specifically at Wimbledon and Roland Garros tournaments 2009. Study results showed the winners to differ statistically significantly from the losers in total sample including players from both tournaments in all variables except for those describing service speed. Like the sample in total, the winners at Wimbledon were superior in all variables, which was most pronounced in the percentage of points won to the opponent`s service, percentage of points won by first and second service, percentage of break points, percentage of net points, and number of aces and winners. The winners at Roland Garros may be efficient due to the high quality of play to their own and the opponent`s service. In conclusion, Wimbledon winners are characterized by the variables related to service which the players rely on, while Roland Garros winners are characterized by baseline play predominated by basic strokes.